"The Inward Eyes of the Kwisatz Haderach:" Jungian Archetypes and Individuation in Frank Herbert's Dune - Elliott, Benjamin Bowers (My University, 2022)
In this analysis, Jungian concepts such as the anima, animus, and individuation are placed onto the events, characters, and philosophies of Frank Herbert’s Dune. In its second chapter, Dune’s all-female monastic order, the Bene Gesserit, are connected with the Jungian anima and the unconscious. Here, the Bene Gesserit’s philosophy is shown to embrace many qualities of the anima, something that allows insight into their passive, observation-focused philosophy. In its third chapter, Dune’s all-male Great House leaders are analyzed through the Jungian animus and logos, something that helps explain Dune’s strength-based, shadowy politics. These two ideologies gestate within the psyche of the novel’s young protagonist, Paul Atreides, and, in this analysis’s fourth chapter, Paul’s character and actions are understood as an “individuation” process. Here, his relationship with each archetype/ their associated faction foreshadows Paul’s later actions, and, in understanding his development, audiences gain a deeper understanding of what qualities within Paul make him, ultimately, a destructive and power-hungry leader. The analysis closes by exploring the scholastic ramifications of a Jungian Dune reading. Keywords: Anima, Animus, Dune, Herbert, Individuation, Jung
I. INTRODUCTION 1 -- Historical Context 4 -- Review of Literature 5 -- Restatement and Significance of Project 15 -- Articulation of Analytical Chapters 17 -- II. “THE WEIRDING WAY”: THE BENE GESSERIT, THE UNCONSCIOUS, -- AND THE ANIMA 21 -- The Unconscious and Anima 22 -- The Anima and the Unconscious in Herbert’s Dune 26 -- Conclusion 34 -- III. “A RULE OF THE EYE AND CLAW:” THE GREAT HOUSES, THE -- ANIMUS, AND LOGOS 35 -- Animus, Logos, and the Shadow 36 -- Qualities of the Animus in Dune’s Great House Leaders 42 -- Mentats as Diseased Logos in Dune 52 -- Two Graves: The Violent Animus and Psychological Wellness 54 -- Conclusion 55 -- IV. “GREAT AND TERRIBLE PURPOSE”: INDIVIDUATION AND -- INITIATION IN FRANK HERBET’S DUNE 56 -- Individuation Demystified 57 -- Paul as Undefined Youth 60 -- Training, Trials, and Lessons of Anima Initiation in Dune 60 -- Training, Trials, and Lessons of Animus Initiation in Dune 65 -- Conclusion 70 -- V. CONCLUSION 71 -- Jungian Analysis in Humanistic Sci-Fi 72 -- Jungian Analysis in Hero Myths 72 -- Jungian Analysis as Mindset Critique 74 -- Jungian Analysis as a Logical Extension of Existing Scholarship 75 -- Jungian Analysis in Herbert’s Dune Sequels 75 -- Conclusion 76 -- VI. WORKS CITED 77
Keywords: Academic theses; Anima (Psychoanalysis); Animus (Psychoanalysis) in literature; Dune (Imaginary place); Dune series (Herbert, Frank); English literature; Herbert, Frank; Individuation (Philosophy) in literature; Jungian psychology; Literature; Psychology